2019
DOI: 10.1002/adfm.201907089
|View full text |Cite
|
Sign up to set email alerts
|

Aqueously Cathodic Deposition of ZIF‐8 Membranes for Superior Propylene/Propane Separation

Abstract: Electrochemical deposition has emerged as a novel approach to fabricate metal–organic framework (MOF) films. Here, for the first time, an aqueously cathodic deposition (ACD) approach is developed to fabricate ZIF‐8 type of MOF membranes without addition of any supporting electrolyte or modulator. The fabrication process uses 100% water as the sole solvent and a low‐defect density membrane is obtained in only 60 min under room temperature without any pre‐synthesis treatment. The membrane exhibits superior perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 32 publications
(29 reference statements)
1
67
0
Order By: Relevance
“…further developed electrochemical deposition using water as the solvent without addition of any electrolyte or modulator. [ 72 ] Vapor deposition is also a simple and controllable process, such as the gel–vapor deposition (GVD) method (Figure 8b). [ 73 ] However, solvent cannot be avoided during the overall GVD process.…”
Section: Membranes: Chemistries Materials and Structuresmentioning
confidence: 99%
“…further developed electrochemical deposition using water as the solvent without addition of any electrolyte or modulator. [ 72 ] Vapor deposition is also a simple and controllable process, such as the gel–vapor deposition (GVD) method (Figure 8b). [ 73 ] However, solvent cannot be avoided during the overall GVD process.…”
Section: Membranes: Chemistries Materials and Structuresmentioning
confidence: 99%
“…Metal organic framework (MOF) membranes have received a great deal of attention over the years due to their potential for use in high-efficiency gas and liquid purification [ 15 , 63 , 64 ]. Among the large family of MOF membranes, ZIF membranes, consisting of zinc ions bridged with the imidazolate ligands show great potential for hydrocarbon separations [ 63 , 65 , 66 , 67 , 68 , 69 , 70 ]. In this section, we mainly focus on the development of ZIF-8 and ZIF-67 membranes for the C 3 H 6 /C 3 H 8 separation based on many reported studies.…”
Section: Current Membrane Materials For C 3 H 6 /C 3 H 8 Sepamentioning
confidence: 99%
“…The evaluation of single gas permeation measurement clearly indicated that the ideal C 3 H 6 /C 3 H 8 selectivity increased with the IPTES density and approached 36, with a C 3 H 6 permeance of 8.5 × 10 −8 mol m −2 s −1 Pa −1 (254 GPU). Recently, an aqueously cathodic (ACD) deposition strategy was developed for the preparation of ZIF-8 membranes by Wei et al, as shown in Figure 6 c [ 69 ]. No electrolyte, modulator, or organic solvent was added during the synthesis procedure, and thus, this is an eco-friendly and energy-saving approach.…”
Section: Current Membrane Materials For C 3 H 6 /C 3 H 8 Sepamentioning
confidence: 99%
“…X‐ray photoelectron spectroscopy (XPS) characterization (Figure 2; Figure S4, Supporting Information) confirms that the LC‐MOF membranes show lower binding energy compared with MOF particles, resulting from large increases in the amount of open metal sites and decreases in the crystallinity. [ 15 ] This may be attributed to the following factor. During LC‐MOF membrane formation, the organic interface layer was immersed into a pure methanol solution.…”
Section: Figurementioning
confidence: 99%